Fast time-varying channels in MIMO-OFDM system using different diversity technique / Nadiah Amaram - Amaram, Nadiah (2013)
The combination of multiple input and multiple output (MIMO) technology and Orthogonal Frequency Divison Multiplexing (OFDM) provide robust to multipath delay and high data rates in wireless communication. The wireless connection of fast moving platforms leads high demands for the applied transmission scheme because of that a channel estimation technique using fast time varying channel is proposed in this paper.